L’adeguamento di Heinrich Rickert al nazionalsocialismo (per il 27 gennaio 1998) - Fulda, Hans Friedrich (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2026)
The neo-Kantian philosopher Heinrich Rickert, at the age of seventy in 1933 delivered a lecture course on Fichte in which he declared his sympathy for the Nazi "national uprising". Fulda shows that Rickert's alignment was not a sudden act of opportunism but stemmed from long-standing philosophical convictions rooted in his theory of values. Rickert subordinated universalistic values (human rights, democracy) to the value of the nation, understood as a good of "present life". Furthermore, he believed that in times of crisis, philosophy should adapt its worldview to the "demand of the day" dictated by the nation-state. Fulda highlights how this position made him blind to the regime's crimes, preventing him from defending Jewish colleagues or the principles of the rule of law. The author concludes that Rickert's thought, though not antisemitic, already contained in its theoretical presuppositions the seeds of a dangerous vulnerability to totalitarianism. Rickert; National Socialism; Philosophy of values; Universalism.